PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KETERAMPILAN GENERIK SAINS SISWA KELAS XI IPA SMA NEGERI 1 PANGKAJENE SIDRAP - Haryanti Putri Rizal; Muhammad Danial (Bioedukasi Jurnal Pendidikan Biologi, 2014)
This research was a quasi experimental aimed to investigate the influenced of inquiry learning model to generic science skills of students class XI IPA SMAN 1 Pangkajene Sidrap on buffer solution subject matter. Research design used “Nonequivalent Control Group Design” that consist of two variable there are inquiry learning model as dependent variable and generic science skills as independent variable. Population in this research is students class XI IPA SMAN 1 Pangkajene Sidrap academic year 2012/2013 which amount 240 students. The sample choosen by class random sampling and have choosen XI IA 1 as experiment class consist of 34 students and XI IA 2 as control class consist of 35 students. Instrument that used is generic science skills test (KGS) were integrated into buffer solution subject matter that includes indirect observation, sense of scale, logical frame, causality, mathematical modeling and concept formation.  The data was collected by given generic science skills test in pretest and posttest by objective test. Data were analyzed by descriptive statistics and inferential statistics. The descriptive results showed that generic science skills student of experiment class get N-gain average 0.71 in high categories and control class get N-gain average 0.31 in medium categories. The inferential statistics analysis showed that tcalculated 7,17 > ttable 1,68 in significant level α = 0.05, so H0 failed or H1 accepted. The result of analysis describe that inquiry learning model have positive influenced to generic skills science of students on buffer solution subject matter.Kata Kunci: Inquiry, Keterampilan Generik Sains